GREEN PURCHASE INTENTION : THE IMPACT OF GREEN BRAND COSMETICS (GREEN BRAND KNOWLEDGE, ATTITUDE TOWARD GREEN BRAND, GREEN BRAND EQUITY) - Maria Angela Diva V.W (Department of Management - Institut Shanti Bhuana, 2020)
Abstract Green marketing is continuously introduced with the aim of developing a green brand and affected on green purchase intention for environmentally conscious consumers. Who will have more information about green product, green brand cosmetics and its performance, will be more aim to purchase it. This study seeks to explore the relationship between green brand knowledge, attitude toward green brand, green brand equity and green purchase intention. This study also examines the effect of green brand on green purchase intention as the consumers’ response to green brand. This research used a quantitative approach. Data collection techniques using a survey using self-administered surveys that are self-managed by distributing questionnaires. The sampling technique used in this study was purposive sampling. Data were collected from 135 consumers of green cosmetics. The hypothesis was tested using Regresion Analysis with SPSS 25. The results showed that green brand knowledge, attitude toward green brand, green brand equity have a positive effect on green purchase intention. Hence, investing in resources that increase these green brand will enhance green purchase intention. Furthermore, this research also found that green brand knowledge, attitude toward green brand, green brand equity have a positive effect simultaneously on green purchase intention among Indonesia green brand cosmetic consumers. Keywords : green brand cosmetic, green brand knowledge, attitude toward green brand, green brand equity, green purchase intetion Abstrak Pemasaran hijau diperkenalkan secara terus menerus dengan tujuan membangun merek hijau dan berdampak pada niat beli hijau konsumen yang focus pada “environmental friendly”. Orang yang memiliki informasi yang lebih terkait produk hijau, merek kosmetik hijau dan kinerja produk/merek tersebut akan lebih memiliki niat untuk membelinya. Penelitian ini bertujuan untuk mengekslore hubungan green brand knowledde, attitude toward green brand, green brand equity dan green purchase intention. Selain itu, penelitian ini juga menguji pengaruh green brand pada green purchase intention, sebagai bentuk respon konsumen terhadap green brand. Penelitian ini menggunakan pendekatan kuantitatif. Teknik pengumpulan data dengan survei menggunakan self-administered survey yang dikelola sendiri dengan menyebarkan kuisoner. Teknik pengambilan sampel yang digunakan dalam penelitian ini adalah purposive sampling. 135 data responden dari konsumen green brand cosmetics diguanakan dalam penelitian ini. Pengujian hipotesis menggunakan Analisis Regresi dengan SPPS 25. Hasil penelitan menunjukkan bahwa green brand knowledge, attitude toward green brand, green brand equity secara signifikan berpengaruh positif pada green purchase intention. Selanjutnya, investasi sumber daya melalui green brand akan meningkatkan green purchase intention, Penelitian ini juga mengemukaka bahwa green brand knowledge, attitude toward green brand, green brand equity secara simultan memberikan pengaruh positif terhadap green purchase intention konsumen green brand cosmetic di Indonesia. Kata Kunci : green brand cosmetic, green brand knowledge, attitude toward green brand, green brand equity, green purchase intetion